2020
DOI: 10.15252/embr.202050274
|View full text |Cite
|
Sign up to set email alerts
|

“Xenotransplantation challenges us as a society”

Abstract: A citizen's conference on xenotransplantation delivers a cautious ‘Yes, but…’ endorsement. It also shows how additional knowledge and debate shifted peoples’ opinion on this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…and ethically justifiable procedures. 141 The pillars in the regulation of xenogeneic heart transplantation are summarized in Figure 6.…”
Section: Regulatory Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…and ethically justifiable procedures. 141 The pillars in the regulation of xenogeneic heart transplantation are summarized in Figure 6.…”
Section: Regulatory Challengesmentioning
confidence: 99%
“…A recent citizens’ conference concluded that the benefits of xenotransplantation outweigh the risks, but strict regulatory measures are required to ensure the development of sustainable and ethically justifiable procedures. 141 The pillars in the regulation of xenogeneic heart transplantation are summarized in Figure 6.…”
Section: Regulatory Challengesmentioning
confidence: 99%
“… 159 , 160 Recent polls in the United States have determined that the general public has an overall positive view towards xenotransplantation. 161 The complex ethical and moral profile surrounding the technology remains an omnipresent concern. There is, however, a growing realization that xenotransplantation could provide critical help to those individuals with life-threatening conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson points to the importance of xenotransplantation if this procedure could be used as a reaction to the organ-shortage [ 78 ]. Kögel and Marckmann, on the other hand, suggest that the use of animal organs in the human body might not change our conception of humanity, but it might influence the human-animal relationship [ 69 ]. Entwistle, Sade, and Drake also focus on the ethical issues surrounding these biomedical interventions, such as animal welfare, assessment of risks, access, financial requirements, or regulatory oversight institutions [ 81 ].…”
Section: Persons With Ad and Special Considerationsmentioning
confidence: 99%